Human Resources Management by Buddhist Ideals of Good Governance in the Digital Era - Pakasagulwong, Pakphathai; Metheevarachatra, Anond (Mahachula Academic Journal, 2021)
This academic article aims to study concept of Human Resources Management by Good Governance and apply the Buddhist Ideals by Dhamma of the Lord Buddha for the Digital Era. In the present world, Even the business organization has a good vision, mission and policy. Although the personnel or staff in the organization do not follow the theory above mentioned, they will not accomplish and achieve their objectives and goals. Consequently, The Personnel management plays an important role and is very important. An obviously, there are inventions for the theories regarding to the personnel management continuously. However, The theories for Human Resources still modern and always be up to date, is the teachings of Lord Buddha. And everything he said is only the truth. Especially “The Seven Sappurisa Dhamma” qualities of a good man, virtues of a gentleman, and apply to the “Good Governance” theory. To show that dhamma of Lord Buddha can be applied to the Human Resources Management and achieving the Human Resources Management success. Because of Buddhism is the science which says about the truth of life and the nature. Good Governance can apply for the personnel in organization very effectively.